The Morality of Disordered Eating and Recovery in Southern Italy. (25th March 2018) - Cheney, Ann M.; Sullivan, Steve; Grubbs, Kathleen
Abstract: Scholars have traced the processes through which moral subjectivities are constituted in culturally meaningful ways through eating disorders and recovery practices, demonstrating how subjective meanings of eating disorders and recovery from them are imbued with moral undertones and become meaningful ways of existing within specific historical and cultural contexts. Drawing on ethnographic insights and interviews with young women with disordered eating histories in southern Italy, we show how suffering from eating disorders and recovery from them enables women to retool their identities and craft moral selves. We draw attention to the value of medical anthropology in the care and comprehension of well‐being of girls and women suffering from disordered eating.